GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 798049435 species occurrences available in GBIF matching the query: All data. The dataset includes 798049435 records from 17242 constituent datasets: Please see http://www.gbif.org/occurrence/download/0013514-170714134226665 for full list of all constituents.
Keywords: GBIF; biodiversity; species occurrences